Collaborative Governance in Developing Tapak Raja Cave Tourism in Wonosari Village, Sepaku, Penajam Paser Utara - Sabat Puji Rahayu Puji; Jumansyah Jumansyah; Muhammad Reza Fahlevy (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2025)
Collaborative Governance is carried out in an effort to solve problems that cannot be solved by an organization such as the development of Goa Tapak Raja Tourism. The study uses a qualitative descriptive method, the data is obtained through observation, interviews and documentation studies. This study uses the Miles, Huberman, and Saldana model data analysis techniques, namely data collection, data condensation, data presentation and drawing conclusions or verification. The results of the study indicate that there is collaborative governance in the development of Goa Tapak Raja tourism between the government, private sector and community. The collaborative activities carried out are very active, providing evidence that the government, private sector and community are supporting factors in the development of Goa Tapak Raja tourism. The increase in the community's economy and tourism potential makes Wonosari Village a tourist village that encourages its people to be active in development. This helps Wonosari Village in facing the progress of the buffer zone of the Indonesian Capital City. However, in the implementation of collaborative governance, there are still problems of abuse of power rights.